Analisis Struktur Komunitas Hutan Bakau Di Pantai Paradiso Kelurahan Oesapa Barat Kecamatan Kelapa Lima Kota Kupang - Dance Bobia Mesah; I. Nyoman P. Soetedjo; Moses K. Tokan (Fakultas Teknik Universitas Cenderawasih, 2023)
Mangroves have high ecological and economic value for local communities, as spawning grounds, nursery grounds, feeding grounds for marine life, and act as protection against abrasion. Protected mangrove forests provide many choices for coastal communities to meet economic needs. However, the activities and exploitation of humans that increase from time to time can threaten, destroy and even reduce the stability of the life, quantity and quality of mangrove forests. This study aims to determine the physical and chemical parameters of the environment, the species composition and structure of the mangrove forest community in Paradiso Beach, Oesapa Barat Village, Kelapa Lima District, Kupang City. This research is quantitative descriptive. This research is located at Paradiso Beach, Oesapa Barat Village, Kelapa Lima District, Kupang City. Methods of data collection by making observations and recording the results of observations and interviews in the field, analysis in the laboratory and documentation. Data analysis begins with data collection, data reduction, data presentation and drawing conclusions. The results showed that station I had parameters of temperature (270C), pH (8.08), salinity (20.5‰), DO (6.42mg/l) and station II had parameters of temperature (280C), pH (7.99), salinity (21.7‰), DO (7.43 mg/l), the parameters of the two points of this station meet the environmental quality standards for mangrove forest communities. The composition of mangrove forest types at the two station points only consisted of 3 families with 3 mangrove species, namely Sonnetaria alba, Rhizophora apiculata, and Avicennia alba. Community structures of the mangrove forest at station I and station II were categorized as damaged with rare criteria at the tree level, sapling level and seedling level. Importance Value Index (INP) of station I (258%) and station II (222.1%), this shows that Sonneratia alba has a higher level of spatial tenure in mangrove forest communities, diversity index (H') at station I (0.64) and station II (0.71), this shows that the mangrove forest community has environmental stability. and the uniformity index (J') of station I (0.68) and station II (0.76), this shows an unbalanced distribution pattern between tree species in mangrove forest communities, and dominance index (D) of station I (0,61) and Station II (0.51), this shows the concentration and distribution of the dominant Sonneratia alba species in the mangrove forest community of Paradiso Beach, West Oesapa Village, Kelapa Lima District, Kupang City.